Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given a time-invariant homogeneous dynamic system $x(k +1) = Ax(k)$, where the system matrix is:

$$ A = \begin{bmatrix} 1 & -1 \\ 2 & 4 \\ \end{bmatrix} $$

And an initial state vector $x(0) = \begin{bmatrix}1 \\ 2\end{bmatrix}$, we know that solution is $x(k) = A^kx(0)$:

$$ x(2) = A^2x(0) = \begin{bmatrix}-1 & -5 \\ 10 & 14\end{bmatrix}\begin{bmatrix}1 \\ 2\end{bmatrix} = \begin{bmatrix}-11 \\ 38\end{bmatrix} $$

With the help of basis change (new basis would be a matrix $M$, coordinates vector $z$, $x = Mz$), we could write:

$$ x(k+1) = Ax(k) \\ Mz(k+1) = AMz(k) \\ z(k+1) = M^{-1}AMz(k) $$

Because $A$ is diagonalizable $M^{-1}AM= \Lambda$, we get the solution (with respect of basis $M$):

$$z(k) = \Lambda^kz(0)$$

Once we know $z(k)$ we can compute $x(k) = Mz(k)$.

Computation of $M$,$\Lambda$ and $M^{-1}$

$\Lambda$ is the diagonal matrix with the eigenvalues $\lambda_1...\lambda_n$ while $M$ is the matrix whose columns are the eigenvectors $v_1...v_n$ of $A$:

$$ \lambda_1 = 2, v_1 = \begin{bmatrix}-1 \\ 1\end{bmatrix}, \lambda_2 = 3, v_2 = \begin{bmatrix}-\frac12 \\ 1\end{bmatrix} \\ M = \begin{bmatrix}-1 & -\frac12 \\ 1 & 1\end{bmatrix}, \Lambda = \begin{bmatrix}2 & 0 \\ 0 & 3\end{bmatrix}, M^{-1} = \begin{bmatrix}-2 & -1 \\ 2 & 2\end{bmatrix}, $$

Computation of $z(0)$

Solution of the linear system $Mz(0) = x(0)$, that is:

$$ \begin{bmatrix}-1 & -\frac12 \\ 1 & 1\end{bmatrix}z(0) = \begin{bmatrix}1 \\ 2\end{bmatrix} $$

We get $z(0) = \begin{bmatrix}-4 \\ 6\end{bmatrix}$

Computation of $z(2)$ and $x(2)$

Easily: $$ z(2) = \Lambda^2z(0) = \begin{bmatrix}4 & 0 \\ 0 & 9\end{bmatrix}\begin{bmatrix}-4 \\ 6\end{bmatrix} = \begin{bmatrix}-8 \\ 27\end{bmatrix}\\ x(2) = Mz(2) = \begin{bmatrix}-1 & -\frac12 \\ 1 & 1\end{bmatrix}\begin{bmatrix}-8 \\ 27\end{bmatrix} = \begin{bmatrix}-\frac{11}{2} \\ -19\end{bmatrix} $$

However, result is wrong, it should be $\begin{bmatrix}-11 \\ 38\end{bmatrix}$. Any help?

share|improve this question
add comment

1 Answer

up vote 4 down vote accepted

You've written:

$$z(2) = \begin{bmatrix}4 & 0 \\ 0 & 9\end{bmatrix}\begin{bmatrix}-4 \\ 6\end{bmatrix} = \begin{bmatrix}-8 \\ 27\end{bmatrix}$$

However, it should be:

$$z(2) = \begin{bmatrix}4 & 0 \\ 0 & 9\end{bmatrix}\begin{bmatrix}-4 \\ 6\end{bmatrix} = \begin{bmatrix}-16 \\ 54\end{bmatrix}$$

after which $x(2)$ works out.

share|improve this answer
    
OMG I'm feeling so stupid right now. I've simplified a vector like a fraction, oh my... really thank you!!! –  user34295 Mar 2 '13 at 16:13
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.